Targeted escape of SARS-CoV-2 in vitro from monoclonal antibody S309, the precursor of sotrovimab - Magnus, Clara Luzia; Hiergeist, Andreas; Schuster, Philipp; Rohrhofer, Anette; Medenbach, Jan; Gessner, André; Peterhoff, David; Schmidt, Barbara (Frontiers in Immunology, 2022)
Class 1 and 2 monoclonal antibodies inhibit SARS-CoV-2 entry by blocking the interaction of the viral receptor-binding domain with angiotensin-converting enzyme 2 (ACE2), while class 3 antibodies target a highly conserved epitope outside the ACE2 binding site. We aimed to investigate the plasticity of the spike protein by propagating wild-type SARS-CoV-2 in the presence of class 3 antibody S309. After 12 weeks, we obtained a viral strain that was completely resistant to inhibition by S309, due to successively evolving mutations R346S and P337L located in the paratope of S309. The antibody lost affinity to receptor-binding domains carrying P337L or both mutations, while ACE2 binding was not affected. The resistant strain replicated efficiently in human CaCo-2 cells and was more susceptible to inhibition of fusion than the original strain. Overall, SARS-CoV-2 escaped inhibition by class 3 antibody S309 through a slow, but targeted evolution enabling immune escape and altering cell entry.